PENERAPAN MODEL PEMBELAJARAN QUICK ON THE DRAW DALAM MATA PELAJARAN GEOGRAFI UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK FASE F DI SMAN 1 LUBUK BASUNG - Mutiara Afriani; Dasrizal Dasrizal; Momon Dt. Tanamir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is based on the problem of active learning caused by the lack of students asking questions, no participation in helping friends during discussions, no feedback to students when presenting discussion results. There are no students who refute, provide suggestions or criticize. The aim of this research is to find out and analyze data regarding the application of the Quick On The Draw model in geography learning to increase the activity of phase F students at SMAN 1 Lubuk Basung. The type of research used is quasi-experimental research. The research design used was Pretest-Posttest Control Group Design phase F at SMAN 1 Lubuk Basung which was registered for the 2023 – 2024 academic year consisting of 10 classes with a total of 354 students. The sampling in this study was random sampling where everyone in the entire target population had the same opportunity to be selected. Obtained research results: Application of the Quick on the draw learning model in geography learning to increase the activity of phase F class students at SMA Negeri 1 Lubuk Basung. Geographic learning activities Students in the Phase F9 experimental class at SMA Negeri 1 Lubuk Basung 2023/2024, obtained an average percentage score of 96.2% which is classified as